A New Subfamily of Sucrose Transporters, SUT4, with Low Affinity/High Capacity Localized in Enucleate Sieve Elements of Plants - Weise, Andreas (American Society of Plant Physiologists, 2000)
A new subfamily of sucrose transporters from Arabidopsis (AtSUT4), tomato (LeSUT4), and potato (StSUT4) was isolated, demonstrating only 47% similarity to the previously characterized SUT1. SUT4 from two plant species conferred sucrose uptake activity when expressed in yeast. The K(m) for sucrose uptake by AtSUT4 of 11.6 ± 0.6 mM was ∼10-fold greater than for all other plant sucrose transporters characterized to date. An ortholog from potato had similar kinetic properties. Thus, SUT4 corresponds to the low-affinity/high-capacity saturable component of sucrose uptake found in leaves. In contrast to SUT1, SUT4 is expressed predominantly in minor veins in source leaves, where high-capacity sucrose transport is needed for phloem loading. In potato and tomato, SUT4 was immunolocalized specifically to enucleate sieve elements, indicating that like SUT1, macromolecular trafficking is required to transport the mRNA or the protein from companion cells through plasmodesmata into the sieve elements.